Parenting in families with children with Special Educational Needs: evaluation of parent`s necessities - Felizardo, Sara (2017)
Parenting, defined as the set of actions realized by parents, in order to promote the sons development, using the resources they possess, becomes a challenge of superior difficulty, in families with children with Special Educational Needs. This study was developed with the purpose of evaluating the needs of families with children with Special Educational Needs that receive specialized support respectively: in a Hospital Pediatric service (HP), and in Portuguese Association for Development and Autism Disorders (PADAD) delegation with the objective of optimizing the services. The study had an exploratory nature being used two samples: one of 27 parents from PH and other of 20 parents of PADAD delegation. The instruments used were: a sociodemographic questionnaire and the Family Neecis Survey adapted from the original version (Bailey & Simeonson, 1988; Bailey, Blasco, & Simeonson, 1992). In the two samples, the major needs verified were of .) general information, u) social and family support and of economic nature. Differences between variables show: general information necessity and economical needs related to the two samples. The caregivers or PADAD are the ones showing larger needs of information, and PH caregivers show more necessities of economical nature. These data show significant differences between i) information needs, ii) social and family support, and iii) economical necessities, in function of marital state and age of caregivers were not found. The data also suggests the need of programs focused in children's problematic area, and investment in informal support network, as a way of improving the support of the services.